Integration of hypnosis into pediatric palliative care - Friedrichsdorf, Stefan J.; Kohen, Daniel P. (Annals of Palliative Medicine, 2017)
At least 8 million children would need specialized pediatric palliative care (PPC) services annually worldwide, and of the more than 42,000 children and teenagers dying annually in the United States, at least 15,000 children would require PPC. Unfortunately, even in resource-rich countries the majority of children dying from serious advanced illnesses are suffering from unrelieved, distressing symptoms such as pain, dyspnea, nausea, vomiting, and anxiety. State of the art treatment and prevention of those symptoms requires employing multi-modal therapies, commonly including pharmacology, rehabilitation, procedural intervention, psychology, and integrative modalities. This article describes the current practice of integrating hypnosis into advanced pain and symptom management of children with serious illness. Three case reports of children living with a life-limiting condition exemplify the effective use of this clinical modality to decrease distressing symptoms and suffering. Hypnosis for pediatric patients experiencing a life-limiting disease not only provides an integral part of advanced symptom management, but also supports children dealing with loss and anticipatory loss, sustains and enhances hope and helps children and adolescents live fully, making every moment count, until death.